Knowledge management and its relationship to administrative creativity from the point of view of the principals of public schools in Ajloun Governorate - Alftimat, Atfa Maroof Abdalkareem (Journal of Educational and Psychological Sciences, 2022)
The study aimed at studying study and creativity from the point of view of the principals of public schools in public schools in Ajloun, and the study relied on the study sample from all study population in the study (132) principals and principals, they were chosen intentionally. The results of the study showed that the degree of cognitive management of principals in public schools in Ajloun governorate, from their point of view, came at a high level with an arithmetic average (3.68), and the degree of administrative creativity came at a high level (3.83). Statistical significance at the level of significance between knowledge management (knowledge diagnosis, knowledge generation, knowledge storage, and knowledge distribution) on administrative creativity, The study recommended the necessity for teachers and principals of public schools to preserve the information they obtain and share this information with all their colleagues in order to benefit from it while performing their work, and to conduct more educational studies on knowledge management and administrative creativity in terms of its dimensions and applications in educational institutions and other institutions.